I just finished geometry and im doing algebra II over the summer, so i am having trouble remembering algebra I stuff.
How do you convert an equation from vertex form (I think its vertex form, correct me if im wrong: 2(x-3)^2+2) to standard form. also, i cant remeber if i distibute the 2 before I square it or what. please help me
For an equation like: y = 2(x - 3)2 + 2
you'll want to do the squaring first: y = 2[(x-3)(x-3)] + 2
y = 2[x2 - 6x + 9] + 2
then, distribute: y = 2x2 - 12x + 18 + 2
finally, simplify: y = 2x2 - 12x + 20
If you distributed the 2 first, you would get the wrong answer because, when you squared, you would also
be squaring the 2 and you need to use the 2 only once.